Exploratory analysis of fractured aquifers: A case study for aquifer systems in southern Rio Grande do Sul, Brazil - Gaspar, Mauren; de Oliveira, Christie Helouise Engelmann; Tognoli, Francisco Manoel Wohnrath [UNESP] (Lepidus Tecnologia, 2023)
Hydrogeological studies need characterization of the aquifer systems using qualitative and quantitative data such as lith-ological and hydrogeochemical analysis, specific capacities, flow rate, salinity and pH. This paper presents a hydrogeolog-ical assessment of the southern portion of the Sulriograndense Shield (ESRG), covering 39 municipalities in the Rio Grande do Sul state, southern Brazil. Thus, lineament data extracted from SRTM images, aeromagnetometric data, hydro-geological data from 885 tubular wells and GIS data were integrated for the hydrogeological characterization. The struc-tural evaluation used lineament demarcated after terrain morphology analysis in the SRTM images at the scales of 1:400,000 and 1:250,000. Furthermore, we used structural subdivisions based on aeromagnetometric data. This inte-grated approach helped to identify the morphostructural correlation with the magnetic characteristics and the specific capacity of the wells. The results indicated the occurrence of three geophysical domains for each aeromagnetic treatment (ASA and 1DV). The PDVD1 domain, based on vertical first derivative processing, was identified as a fault core because it does not coincide with producing wells, following NW-SE and, subordinately, SW-SE trends. The PDVD2 domain presents lineaments less persistent with preferential SW-NE orientation and, subordinately, NW-SE, identified as a damage zone for coinciding with crystalline areas bearing wells of higher specific capacity. These structural results reinforce the ESRG's NE-SW and NW-SE trends, following trends within geophysical domains. For the evaluation and classification of the wells, data from 1,495 tubular wells were processed using Python scripts written in the Jupyter notebook platform (format.ipynb). From the 885 filtered wells, 211 wells intersected with 1:400,000 scale lineaments, and 588 wells intersected with 1:250,000 scale lineaments. Therefore, this study corroborates the efficiency with a 1:250,000 scale for regional studies and demonstrates how a programming language is a powerful tool for hydrogeological studies and assessment.
Avaliação da capacidade exploratória de aquíferos fratura-dos: Um estudo de caso para os sistemas aquíferos da por-ção sul do Rio Grande do Sul, Brasil
Keywords: Aerogeophysics; Fractured Aquifers; GeoPandas; Hydrogeology; Python